Mauritius : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The review outlines a simple analytical model to explain the unemployment puzzle, especially the U-curve phenomenon. It analyzes the central institutional imperfections that characterize the existing Mauritian labor market and suggests possible reforms. It also reviews the IMF's projections and estimates on consolidated monetary survey, summary accounts of the Bank of Mauritius, commercial banks and offshore banks, balance of payments, summary of the tax systems and government finances, sugar cultivation, yields and output, real growth rates of expenditure on gross domestic product, gross domestic product real growth rates by industrial origin and at current prices, 1998-2002, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet